Creative Problem Solving and Social Cooperation of Effective Physical Therapy Practice: A Pioneer Study and Overview - Eli Carmeli (The Scientific World Journal)
Action research (AR) has an important role to play in educating physical therapists. Increasing efforts should be encouraged to instigate AR programs in physical therapy practice and clinical education. Such programs commonly require considerable effort and understanding by clinical instructors, and require adoption of new educational methods. AR programs can lead physical therapists and clinicians to be more questioning and reflective in evaluating practical questions regarding patient therapy and education. The purpose of this article is to educate the readers on the importance of AR and to provide a few relevant references on that topic. A specific study is described in this paper in which physical therapy clinical instructors participated in a structured workshop designed to demonstrate the values of AR and how such values can be incorporated in teaching their students. AR can lead to improved therapist-patient interaction and help solve specific practical problems arising during therapy sessions.